Mawson's Mission : Launching Women's Intercollegiate Athletics at the University of Kansas - Mawson, Lora Marlene (Book collections on Project MUSE., 2020)
"Often called the "Mother of KU Women's Athletics," Marlene Mawson was appointed to the physical education faculty at the University of Kansas in 1968. A year later, the newly established national Commission on Intercollegiate Athletics for Women mandated that US colleges and universities provide women's intercollegiate athletics programs. Mawson was charged with establishing the program at KU. "Planning sports competition schedules, staffing coaches, organizing policies and procedures for coaches and athletes, coordinating practice schedules, budgeting, and directing the new KU intercollegiate sports program for women were my responsibilities without much intervention or guidance from anyone else," she writes. "I was on my own, since there was no precedent nor a blueprint for creating a women's athletics program within a meager budget." Despite the challenges, in the first decade KU's were among the leading women's teams when they competed in national championships in volleyball, basketball, softball, and gymnastics. Mawson says, "my passion was always providing for the joy of women to compete in sports." She was inducted into the KU Athletics Hall of Fame in 2009. In this memoir, Mawson describes her remarkable career, from her early years in Missouri to her retirement in 2004. At the end of the book, she includes memories from early KU women athletes"--